Sistem Pengelolaan Kegiatan Perusahaan Menggunakan Identifikasi QR Code - Dani Yusuf; Warta, Joni; Rejeki, Sri (Journal of Informatic and Information Security, 2021)
Activities in a company or institution are something that is usually done, the forms of these activities are generally training, socialization of new regulations, inauguration, and so on. These activities need to be recorded and the data managed as documentation or reference and consideration in subsequent activities. This activity requires planning starting from preparation, scheduling, distributing invitations via email, to implementing and recording the attendance of invited participants. The case study was conducted at PT Pelni Indonesia as an Indonesian National Shipping company that often carries out internal activities within the company. The problem that occurs in the management of company activities at PT Pelni is that so far it is still using the manual system. The participant registration process, participant data collection, sending invitations, recording participant attendance and so on are carried out in handwriting and stored in an excel file. Of course, this makes it difficult to search and manage data, and allows data loss or document slippage to occur. One solution that can be used to overcome these problems is to build an information system for managing company activity data. The management system can assist the HRD for data management needed in the implementation of activities carried out by the company. QR Code technology is also used to encrypt participant invitation numbers, verify participant data and to record attendance. The result of developing this system is a data management system for company activities by utilizing Quick Response Code (QR Code) technology. The generated QR Code can store various participant data in only 1 code and is used to verify participant data.